Medal
Solve the following system of equations by any method.
x + y = 32
x + z = 39
y + z= 47

- anonymous

Medal
Solve the following system of equations by any method.
x + y = 32
x + z = 39
y + z= 47

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- jamiebookeater

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- LynFran

which method u prefer to use

- anonymous

addition

- LynFran

what i meant was elimination , substitution ... matrix

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

substitution

- Hero

Subtract the 2nd from the 1st to get y-z=-7

- Hero

Then you'll have :
y-z =-7
y+z=47
Add the equations together to eliminate z then solve for y.

- Hero

That's the easiest approach here.

- anonymous

y = 0 z = 0

- anonymous

-7 + 47 = 40

- Hero

You should have gotten 2y=40 not y=0

- anonymous

oh sorry i subtracted

- Hero

Yes I know. Be careful

- anonymous

whats the next step

- anonymous

@LynFran do you understand this

- LynFran

here ur substitution method and yes i know all 3 method thats y i ask which u prefer
ok we can rewrite the 3rd equation as y=47-z
we can also rrewrite the 2nd equation to get x=39-z
now subs the 2 equations about into the 1st equation to get
x+y=32
39-z+47-z=32
86-2z=32
86-32=2z
54=2z
27=z
now sub z=27 into the 3rd equation above to get
y+z=47
y+27=47
y=47-27
y=20
now sub y=20 into 1st equation to get
x+y=32
x+20=32
x=32-20
x=12

- Hero

Elimination is the simplest and most efficient method to Use here.

- LynFran

yea i agree but @harz360 prefer substitution

- Hero

The goal is to solve using the least amount of steps

- anonymous

when i see all the steps thats when i understand it

- Hero

It's a matter of efficiency not preference.

- texaschic101

I would have taken the first 2 equations...and eliminated the x's...then go from there

- LynFran

me too

- Hero

Exactly .

- anonymous

but thanks a lott @LynFran

- anonymous

@Hero thanks so much

- LynFran

here the elimination method
using 1st and 2nd equation subtract we get
y-z=32-39
now using the 3rd equation subtract
y-z=-7
y+z=47
we get -z-z=-7-47
-2z=-54
z=-54/-2
z=27
now sub z=27 into 3rd equation we get
y+z=47
y=47-27
y=20
now sub y=20 in 1st equation we get
x+y=32
x+20=32
x=32-20
x=12

- anonymous

this method seems confusing by the subtraction method seems easier to follow

- Hero

That WAS the subtraction method. Lyn just wrote it awkwardly

- anonymous

ohh i c

- LynFran

no thats the elimination method in details

- Hero

Subtraction/Elimination Method

- Hero

Interchangeable description

- anonymous

ohh i understand both when i see the steps which lyn has shown nicely

Looking for something else?

Not the answer you are looking for? Search for more explanations.